2008
DOI: 10.1158/1078-0432.ccr-07-5144
|View full text |Cite
|
Sign up to set email alerts
|

A Metastasis Modifier Locus on Human Chromosome 8p in Uveal Melanoma Identified by Integrative Genomic Analysis

Abstract: Purpose: To identify genes that modify metastatic risk in uveal melanoma, a type of cancer that is valuable for studying metastasis because of its remarkably consistent metastatic pattern and well-characterized gene expression signature associated with metastasis. Experimental Design: We analyzed 53 primary uveal melanomas by gene expression profiling, array-based comparative genomic hybridization, array-based global DNA methylation profiling, and single nucleotide polymorphism^based detection of loss of heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 30 publications
3
70
2
1
Order By: Relevance
“…Several candidates were discovered, and their 3 0 -UTRs (3 0 -untranslated regions) were conjugated with luciferase for reporter assays. LZTS1 has the potential to suppress the invasion and motility of melanoma cells 24 , and its expression is associated with lymph node metastasis in breast cancer patients 25 . In our experiments, the luciferase activity of plasmids containing the 3 0 -UTR of LZTS1 was significantly reduced in the presence of miR-135b ( Fig.…”
Section: Mir-135b Promotes Lung Cancer Cell Growth and Emt In Vitromentioning
confidence: 99%
“…Several candidates were discovered, and their 3 0 -UTRs (3 0 -untranslated regions) were conjugated with luciferase for reporter assays. LZTS1 has the potential to suppress the invasion and motility of melanoma cells 24 , and its expression is associated with lymph node metastasis in breast cancer patients 25 . In our experiments, the luciferase activity of plasmids containing the 3 0 -UTR of LZTS1 was significantly reduced in the presence of miR-135b ( Fig.…”
Section: Mir-135b Promotes Lung Cancer Cell Growth and Emt In Vitromentioning
confidence: 99%
“…In 1996, Prescher et al showed a strong correlation between chromosome 3 loss and metastatic death (10). Since then, other chromosomal abnormalities have been shown to correlate with poor prognosis and these include: 8q gain; 8p loss; 1p loss; 6q loss and lack of 6p gain (11)(12)(13). White et al suggested that chromosome 3 loss correlated with metastatic death only if combined with chromosome 8 gain (henceforth, summarized by us as "C38A" for "chromosome 3 and 8 abnormality"; ref.…”
mentioning
confidence: 99%
“…Moreover overexpression of LZTS1 in metastasizing uveal melanoma-derived cells inhibited their motility and invasion (Onken et al, 2008).…”
Section: Uveal Melanomamentioning
confidence: 97%